(untitled) (Research, Society and Development, 2023)
The object of this study is the principle of temporality, analyzed through the succession to the position of Governor of the State of Rio Grande do Norte during the decade that corresponds to the years 1975 and 1986, a period marked by the Military Dictatorship in Brazil. Using mainly empirical and qualitative bibliographic research in the historical and legal literature on the subject, this work aims to attest that, although three different rulers have exercised their mandates, the principle of temporality was not followed, as well as that of alternation of power. The justification of this study is based on the relevance of the theme in a society whose regime is democratic and defined by popular participation. In view of the principle of temporality, the holder of the Public Power must be alternated, however, as will be demonstrated in a more in-depth analysis, this legal institute was not observed in this period, with only a simulation of normality.